Sectorial Output Growth and Commercial Bank Credit Nexus in Nigeria - Adedigba Praise Abina; Emeka Obi (Quantitative Economics and Management Studies, 2020)
This study investigates the nexus between sectorial output growth and commercial bank credit in Nigeria. Sectorial output growth was broken down into three different proxies which include production sector, Commercial sector and Service sector contribution to gross domestic product while bank credit to production sector, general commerce and service sector served as the independent variables which are used to proxy commercial bank credit. The study made use of secondary data obtained from Central Bank of Nigeria Statistical bulletin for the period 1981 to 2019. It employed Descriptive Statistics, Phillips-Perron (PP) Unit Root Test, Simple Regression Analysis and Granger Causality Test. The Granger Causality result showed that bi-directional causality is identified in the three models while there were positive and significant relationship between bank credit to production sector, general commerce, service sector and production sector contribution to gross domestic product, general commerce sector contribution to gross domestic product and service sector contribution to gross domestic product respectively. The paper therefore recommends that the regulatory authorities should prioritize more on increasing and easing the requirements needed from deficit spenders to secure credit from commercial banks in Nigeria.